ANALISIS KUALITAS WEBSITE LINTASARTA.NET MENGGUNAKAN METODE WEBQUAL 4.0 DI PT. LINTASARTA JAKARTA PUSAT - Dedi Irawan; Sulistianto Sutrisno Wanda (UNIVERSITAS STEKOM, 2023)
Website is a form of mass media that is published through internet network that can be accessed anywhere and anytime. To know the quality of a website it is necessary to measure, by doing measurement of the quality of a website can be known user satisfaction against the website. In this study using the WebQual 4.0 method refers to the three core dimensions representing the quality of a Website, namely usability, Information Quality, Service Interaction Quality. This research was conducted using a questionnaire the population of this study were Lintasarta employees, sample from this study 28 questionnaires. After the data is obtained, it is tested for validity and reliability. In this study, the regression analysis used the assumption test classical, and multiple linear analysis. Then for hypothesis testing F test and t test are used. The results obtained in this study are Usability Quality, Information Quality and Interaction quality have a positive effect on consumer satisfaction.